Meconopsis (sect. Grandes) Fedde, Engl., Pflanzenr. ... - Elvebakk, Arve; Bjerke, Jarle W. (Zenodo, 2024)
4.4.Meconopsis sect. Grandes(Prain.) Fedde, Engl., Pflanzenr. 4, 104: 262. 1909 Type species. Meconopsis grandis Prain. Notes. Grey-Wilson (2014) included four conspicuously yellow species in Section Grandes (Prain) Fedde. Subsequently, two additional species were added to the section; one is the new species, M. wanbaensis Tosh. Yoshida (Yoshida 2019), the other is the recombined M. uniflora (C. Y. Wu & H. Chuang) Tosh. Yoshida et al. (Yoshida et al. 2019). Whereas almost all Meconopsis species described after the publication of the monograph by Grey-Wilson (2014) are monocarpic and, in the case of the Forrestianae and Impeditae, rather small plants, one large and blue perennial poppy has also been described. This is M. gakyidiana Tosh. Yoshida et al., the famous blue poppy of Bhutan, which is also the country’s national flower (Yoshida et al. 2016 b). It has remained in cultivation since George Forrest’s introduction in the 1930 s, partly under various cultivar names (Grey-Wilson 2017), partly as M. ... : Published as part of Elvebakk, Arve & Bjerke, Jarle W., 2024, Papaver recircumscribed: A review of neighbouring Papaveraceae genera, including Afropapaver nom. et stat. nov. and Oreomecon, a large, Arctic-Alpine genus, pp. 105-188 in PhytoKeys 248 on pages 105-188, DOI: 10.3897/phytokeys.248.121011 ...